Dampak Pengalihan Lahan Mangrove Terhadap Keanekaragaman Benthos di Kecamatan Jaya Baru Kota Banda Aceh - Fitria Ulfa; Muhammad Ali Sarong; Abdullah Abdullah (Biotik, 2016)
This study aims to determine the impact of the land transfer to the diversity of mangrove benthos in the district of Banda Aceh Jaya Baru. This research was conducted in September-November 2014 in an area of mangrove Jaya Baru sub-district of Banda Aceh. The method used survey method or direct observation. Stations were divided into four stations using purposive sampling method on the basis of the existence of mangrove. Benthos diversity analyzed by formula diversity index, while the impact of the transfer was analyzed with the description. The results obtained by analysis of benthos diversity on land that has been reclaimed 1.18 and on land that is not reclaimed 1,17. The conclusion is the diversity of benthos was proving that the land transfer mangrove in the district of Banda Aceh Jaya Baru impact on the benthos diversity that needs to be disseminated and awareness-raising so that the mangrove ecosystem is maintained.